2009
DOI: 10.1111/j.1751-908x.2009.00907.x
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for Quantitative Detection of Elemental Sulfur and Polysulfide Zero‐Valent Sulfur Distribution in Natural Aquatic Samples

Abstract: A HPLC‐based protocol has been developed for the determination of zero‐valent sulfur (ZVS) speciation, including solid, colloidal elemental sulfur and individual inorganic polysulfides in natural aquatic samples. The protocol includes four experimental procedures: (1) determination of polysulfide speciation by rapid single‐phase derivatisation with methyl trifluoromethanesulfonate; (2) determination of the sum of polysulfide and colloidal sulfur by reaction with hydrogen cyanide (cyanolysis); (3) determination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 94 publications
(173 reference statements)
1
76
0
Order By: Relevance
“…It provides the major improvement of the method performance compared with cyanolysis with ion-chromatography finishing (detection limit 2 µmol L -1 , as reported by Kamyshny et al [2008]), photometric finishing (detection limit 10 µmol L -1 , as reported by Kamyshny et al [in press ]), and cyanolysis in organic solvents (150 µmol kg -1 sediment, as reported by Troelsen and Jørgensen [1982] and 100 nmol L -1 , as reported by Jacobs and Emerson [1982]). …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It provides the major improvement of the method performance compared with cyanolysis with ion-chromatography finishing (detection limit 2 µmol L -1 , as reported by Kamyshny et al [2008]), photometric finishing (detection limit 10 µmol L -1 , as reported by Kamyshny et al [in press ]), and cyanolysis in organic solvents (150 µmol kg -1 sediment, as reported by Troelsen and Jørgensen [1982] and 100 nmol L -1 , as reported by Jacobs and Emerson [1982]). …”
Section: Discussionmentioning
confidence: 99%
“…The final pH value of the colloidal ZVS was 2.3. At this pH value, more than 99.97% of ZVS was in the form of colloidal sulfur and only 0.027% in the form of polysulfides (calculated from the set of thermodynamic constants from Kamyshny et al [2007]). Polysulfide ZVS standards and colloidal ZVS standards were used for not more than 4 h after preparation.…”
Section: Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Sulfide oxidation intermediates, which have sulfur-sulfur bonds, are known to be reactive toward free cyanide (Kelly et al 1969;Szekeres 1974;Luthy and Bruce 1979;Kamyshny 2009;Kamyshny et al 2009). Polysulfides, polythionates with four or more sulfur atoms, and soluble and colloidal elemental sulfur react with cyanide faster than trithionate and thiosulfate (Kelly et al 1969;Luthy and Bruce 1979;Kamyshny et al 2009). Polysulfides are known to react rapidly with hydrogen cyanide via:…”
Section: Delaware Great Marsh Sedimentsmentioning
confidence: 99%